(untitled) (Innovative professional education, 2025)
The article analyzes the transformational processes in vocational education in Ukraine caused by the war, the need for post-war recovery, and the desire for European integration. Key challenges such as infrastructure destruction, changing labor market needs, and the need to adapt to European standards are considered. Special attention is paid to innovative approaches to learning, the development of digital skills, and cooperation with international partners